Analisis Hubungan Kelengkapan Pengisian Resume Medis Terhadap Kesesuaian Standar Tarif INA-CBG’s Instalasi Rawat Inap Teratai RSUP Fatmawati Jakarta - Apriyantini, Dewi (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2016)
This research discussed on the completeness of medical resume (primary diagnostic, secondary diagnostic and major procedure) in consistency with INA-CBGs costing at Teratai Inpatient Instalation Central General Hospital (RSUP). This research used mix methods approach with cross sectional design. This research found that there is still incompleteness in filling medical records especially for primary diagnostic, secondary diagnostic and major procedure that potentially may cause inconsistency with INA-CBSs costing. The incompleteness were caused by many factors, and this research suggest to conduct evaluation and socialization of the Standard Procedure Operational (SPO), the implementation of reward and punishment system, monitoring and evaluation on medical record forms, addition of book or list of diagnostic code, upgrading of INA-CBGs software.